Impact of the Cationic Moiety of Ionic Liquids on Chemoselective Artificial Olfaction - Oliveira, Ana Rita (2023)
Funding Information: This research was funded by the European Research Council (ERC) under the EU Horizon 2020 research and innovation program [grant reference SCENT-ERC-2014-STG-639123, 2015–2022, and Grant Agreement No. 101069405─ENSURE─ERC-2022-POC1]. Publisher Copyright: © 2023 The Authors. Published by American Chemical Society.